Antiestrogen therapies affect tissue homeostasis of the gerbil (Meriones unguiculatus) female prostate and ovaries - Santos, Fernanda C. A.; Custodio, Ana M. G.; Campos, Silvana G. P. [UNESP]; Vilamaior, Patricia S. L.; Goes, Rejane M. [UNESP]; Taboga, Sebastiao R. [UNESP] (Soc Study Reproduction, 2008)
The present work aims to evaluate the response of the adult gerbil female prostate (paraurethral glands) and ovaries to short-term exposure to antiestrogenic agents, consisting of daily oral doses of letrozole (1 mg kg(-1) day(-1)) or intradermal doses of tamoxifen (1 mg/kg) every other day for 21 days. The serum levels of testosterone and estradiol were monitored, and the prostates and ovaries collected for structural, ultrastructural, and immunocytochemical analyses. The letrozole treatment resulted in increases of serum testosterone levels and secretory activity as well as in glandular hyperplasia and dysplastic growth, simulating the effects caused by the exogenous androgens. The effects caused by tamoxifen indicate that this endocrine agent acted as an estrogenic agonist on the prostate, causing glandular hypertrophy, secretory activity decrease, and the development of prostatic lesions. Therefore, it is possible to conclude that the letrozole and tamoxifen therapies result in a series of complex effects that endanger the physiology of hormone-dependent organs, including the female prostate and ovaries. The hormonal imbalance caused by administration of these drugs resulted in considerable changes in prostatic morphology, in a manner very similar to what occurs during the development of prostatic lesions in aged postmenopausal women. Thus, these therapies must be chosen carefully since long-term treatments can result in female prostate dysplasic lesions.
Keywords: androgens; estradiol; female prostate; female reproductive tract; letrozole; morphology; ovary; prostate; tamoxifen